El valor de la intimidad: Una constante en la poesía de Julieta Dobles Izaguirre - Vallejos Ramírez, Mayela (2004)
The purpose of this essay is to analyze in general the entire work of Julieta Dobles. This will allow appreciating the multiple stages that the poet has developed through the years. We will accomplish it by analyzing a few poems from each of her books.